A Novel Power Factor Correction Rectifier for Enhancing Power Quality - Bindu K V; B Justus Rabi (International Journal of Power Electronics and Drive Systems (IJPEDS), 2015)
In this paper, the disturbances in power system due to low quality of power are discussed and a current injection method to maintain the sinusoidal input current which will reduce the total current harmonic distortion (THD) as well as improve the power factor nearer to unity is proposed. The proposed method makes use of a novel controlled diode rectifier which involves the use of bidirectional switches across the front-end rectifier and the operation of the converter is fully analyzed. The main feature of the topology is low cost, small size, high efficiency and simplicity, and is excellent for retrofitting front-end rectifier of existing ac drives, UPS etc. A novel strategy implementing reference compensation current depending on the load harmonics and a control algorithm for three-phase three-level unity PF rectifier which draws high quality sinusoidal supply currents and maintains good dc link- voltage regulation under wide load variation. The proposed technique can be applied as a retrofit to a variety of existing thyristor converters which uses three bidirectional switches operating at low frequency and a half-bridge inverter operating at high frequency .The total power delivered to the load is processed by the injection network, the proposed converter offers high efficiency and not only high power factor but also the Total Harmonic Distortion is reduced. Theoretical analysis is verified by digital simulation and a hardware proto type module is implemented in order to confirm the feasibility of the proposed system. This scheme in general is suitable for the common variable medium-to high-power level DC load applications.